Towards personalized web-tasking: Task simplification challenges (2013)
Despite the increasing use of the web to support human activities, most web interactions required to accomplish personal goals are performed manually by users. Even though users can easily transform a goal into multiple web interactions, the manual governance of these interactions diminishes the user experience. Personalized web-tasking seeks to improve the user experience by automating personal web tasks. This automation is driven by user needs, matters of concerns, and personal context. An important concern in personalized web-tasking is task simplification, the process of decomposing a personal web task into simpler tasks that can readily be composed into bigger tasks. This position paper characterizes a set of task simplification challenges intended as starting points for advancing the field of personalized web-tasking.